Kierunki kształtowania strategii konkurencji przedsiębiorstw przemysłu spożywczego po przystąpieniu Polski do Unii Europejskiej - Szwacka-Salmonowicz, Joanna (Directions of Competition Strategies Creation of Food Companies after Polish Accession to the EU, 2005)
The aim of this article is to present the direction of differentiation strategies of food-industry enterprises in the context of EU integration.The crucial sources of competitive advantage are described. The analysis of competitiveness of Polish food sector is based on Porter's five forces. It recommends to concentrate on strategies of lowest costs and prices, differentiation and corporation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 338-342